A Review of a Successful Unsubsidized Market-Based Rural Solar Development Initiative in Laikipia District, Central Kenya - O. Wambuguh (International Journal of Renewable Energy Development, 2013)
The development of renewable energy technologies (RETs) in many areas far from grid-based electricity have primarily involved solar photovoltaics (SPVs) which tap solar radiation to provide heat, light, hot water, electricity, and cooling for homes, businesses, and industry. A study on RETs took place in the Wiyumiririe Location of Laikipia District (north-central Kenya), a rich agricultural region. To explore this solar initiative in such a remote part of the country, a purposive randomized convenience sample of 246 households was selected and landowner interviews conducted, followed by field visits and observations. Although more than half of the households visited had SPV installations, solar energy was found to contribute only 18% of household estimated total energy needs; most residents still primarily relying on traditional energy sources. Several types of solar panels of different capacities and costs were utilized. Many landowners had at least one or two rooms using solar energy for household lighting, for appliance charging and to power radio and television. Almost all respondents appreciated that solar energy was clean renewable energy that greatly improved household living conditions; gave them some prestige; was easy to use and maintain; and was available year around. Although such significant benefits were associated with SPVs, only about 40% of residents interviewed were somehow satisfied with its development. Respondents expressed specific developmental initiatives that were closely associated with the availability of solar energy. Nevertheless, a number of challenges were raised associated with SPVs primarily investment capital and equipment costs and maintenance. As solutions to capital building will not solely rely on subsidies or individual farmer inputs, strategies must be found to mobilize the essential and tested tools for success including sustainable capital generation, building local institutions and capacities that integrate rural people, local participation in rural development activities and public education and training. Keywords: appliance charging,battery,development initiatives, household lighting, landowners,solar energy, SPVs, solar equipment and accessories